A Green Halal Tourism as a Conceptual Framework for Supporting Sustainable Tourism: A Literature Review - Kuncorosidi Kuncorosidi (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2026)
Sustainable tourism and halal tourism have emerged as prominent discourses in tourism studies; however, they are often examined as separate domains within the literature. While sustainable tourism emphasizes the balance between environmental, social, and economic dimensions, halal tourism has predominantly been framed in terms of Sharia compliance and market segmentation. This article aims to conceptualize green halal tourism as an integrative framework for supporting sustainable tourism through a conceptual literature review approach. Drawing on a systematic synthesis of peer-reviewed literature on halal tourism, green tourism, and sustainable tourism, this study identifies conceptual intersections, theoretical gaps, and opportunities for integration across these domains. The synthesis indicates that green halal tourism can be understood as a conceptual framework that integrates halal values as an ethical foundation, green tourism practices as operational mechanisms, and sustainable tourism as a strategic outcome. This framework highlights the potential role of halal values in strengthening the internalization of sustainability principles within tourism practices, particularly across environmental, social, and economic dimensions. Theoretically, this study contributes to the sustainable tourism literature by explicitly incorporating value-based and ethical perspectives into sustainability frameworks. The proposed conceptualization also provides a foundation for future empirical research to operationalize and examine green halal tourism across diverse tourism contexts